Validation of Deleterious Mutations in Vorderwald Cattle - Reinartz, Sina (PLoS One, 2016)
In Montbéliarde cattle two candidate mutations on bovine chromosomes 19 and 29 responsible for embryonic lethality have been detected. Montbéliarde bulls have been introduced into Vorderwald cattle to improve milk and fattening performance. Due to the small population size of Vorderwald cattle and the wide use of a few Montbéliarde bulls through artificial insemination, inbreeding on Montbéliarde bulls in later generations was increasing. Therefore, we genotyped an aborted fetus which was inbred on Montbéliarde as well as Vorderwald x Montbéliarde crossbred bulls for both deleterious mutations. The abortion was observed in an experimental herd of Vorderwald cattle. The objectives of the present study were to prove if one or both lethal mutations may be assumed to have caused this abortion and to show whether these deleterious mutations have been introduced into the Vorderwald cattle population through Montbéliarde bulls. The aborted fetus was homozygous for the SLC37A2:g.28879810C>T mutation (ss2019324563) on BTA29 and both parents as well as the paternal and maternal grandsire were heterozygous for this mutation. In addition, the parents and the paternal grandsire were carriers of the MH2-haplotype linked with the T-allele of the SLC37A2:g.28879810C>T mutation. For the SHBG:g.27956790C>T mutation (rs38377500) on BTA19 (MH1), the aborted fetus and its sire were heterozygous. Among all further 341 Vorderwald cattle genotyped we found 27 SLC37A2:g.28879810C>T heterozygous animals resulting in an allele frequency of 0.0396. Among the 120 male Vorderwald cattle, there were 12 heterozygous with an allele frequency of 0.05. The SLC37A2:g.28879810C>T mutation could not be found in further nine cattle breeds nor in Vorderwald cattle with contributions from Ayrshire bulls. In 69 Vorderwald cattle without genes from Montbéliarde bulls the mutated allele of SLC37A2:g.28879810C>T could not be detected. The SHBG:g.27956790C>T mutation appeared unlikely to be responsible for the present case of abortion and, in addition, we observed this mutation in a homozygous state in a living animal. In conclusion, we could demonstrate the first case of an aborted fetus carrying the deleterious SLC37A2:g.28879810C>T mutation homozygous and show that this deleterious mutation had been introduced through Montbéliarde bulls into Vorderwald cattle.